Penerapan Nilai-Nilai Religius Santri Melalui Program Tahfidz Menginap di Rumah Qur’an - Nur Aidila Fitria; Muhammad Yoga Julyanur; Eko Nursalim (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
The world of education today, especially Qur'anic education, has many challenges. This can be seen from children's excessive obsession with gadgets that make their religious character seem to be eroded by the sophistication of the times marked by the rapid advancement of information and technology. Therefore, it is important to know that instilling religious values early on in children is very important. This research uses a descriptive type qualitative approach by collecting data through an unstructured interview process. This study aims to analyze how the application of religious values through the "Tahfidz Menginap" program in order to shape the character of students at the Ridhotullah Qur'an House Sangatta for the better. As a result, there are several points of religious values that are taught, applied, and internalized in students, namely honesty, discipline, patience, responsibility, and cleanliness. Finally, it can be concluded that the application of religious values is very crucial to be taught to children so that they can implement it in their daily lives so that they grow into individuals with character.